2019
DOI: 10.3747/co.26.4377
|View full text |Cite
|
Sign up to set email alerts
|

Lazarus-Type Tumour Response to Therapy with Nivolumab for Sarcomatoid Carcinomas of the Lung

Abstract: Pulmonary sarcomatoid carcinoma (psc) is a rare subtype of non-small-cell lung carcinoma with a poor prognosis and poor response to chemotherapy and radiotherapy. A previous study reported that psc expresses high levels of PD-L1, suggesting the potential efficacy of immune checkpoint inhibitors in these tumours. We report 2 cases of patients with a lung sarcomatoid carcinoma. Both patients initially underwent curative lung resection, but developed early recurrent disease. Because PD-L1 was highly expressed in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…Thus, PD-1/PD-L1 immunotherapy might be one of the most effective ways to treat this disease. 81 Some researchers believed that PSC patients had significant differential expression of PD-L1 compared with that of NSCLC patients. When PD-L1 is negative, immunotherapy can still be effective due to the interaction between the immune system and the tumor.…”
Section: Treatmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, PD-1/PD-L1 immunotherapy might be one of the most effective ways to treat this disease. 81 Some researchers believed that PSC patients had significant differential expression of PD-L1 compared with that of NSCLC patients. When PD-L1 is negative, immunotherapy can still be effective due to the interaction between the immune system and the tumor.…”
Section: Treatmentsmentioning
confidence: 99%
“…The patients still recovered well after a year of follow up. 66 , 76 , 81 However, another study showed one patient with stage IV disease, who had received first-line and second-line chemotherapy, gained no benefit after surgery. After treatment with nivolumab, this patient’s symptoms improved, the brain damage resolved, and reactions occurred at other metastatic sites.…”
Section: Treatmentsmentioning
confidence: 99%
“…The clinical behaviour of PSCs is extremely aggressive, and patient prognosis is extremely poor (2,3), since these tumours have a high rate of distant metastasis. The effect of conventional chemotherapy for PSCs remains controversial due to their low incidence (4); thus, progress on tumour treatments is moderate.…”
Section: Introductionmentioning
confidence: 99%
“…Several experiences have recently supported this view on clinical ground, evidencing extraordinary response to nivolumab. [20][21][22] For this, it is essential to be aware of sarcomatoid spindle cell carcinomas mimicking nonneoplastic conditions to ensure a correct diagnosis but also alternative effective treatments.…”
Section: Discussionmentioning
confidence: 99%